Establishment of a high-resolution 3D modeling system for studying pancreatic epithelial cell biology in vitro - Bakhti, Mostafa; Scheibner, Katharina; Tritschler, Sophie; Bastidas-Ponce, Aimee; Tarquis-Medina, Marta; Theis, Fabian J.; Lickert, Heiko (Molecular Metabolism, 2019)
Objective: Translation of basic research from bench-to-bedside relies on a better understanding of similarities and differences between mouse and human cell biology, tissue formation, and organogenesis. Thus, establishing ex vivo modeling systems of mouse and human pancreas development will help not only to understand evolutionary conserved mechanisms of differentiation and morphogenesis but also to understand pathomechanisms of disease and design strategies for tissue engineering. Methods: Here, we established a simple and reproducible Matrigel-based three-dimensional (3D) cyst culture model system of mouse and human pancreatic progenitors (PPs) to study pancreatic epithelialization and endocrinogenesis ex vivo. In addition, we reanalyzed previously reported single-cell RNA sequencing (scRNA-seq) of mouse and human pancreatic lineages to obtain a comprehensive picture of differential expression of key transcription factors (TFs), cell–cell adhesion molecules and cell polarity components in PPs during endocrinogenesis. Results: We generated mouse and human polarized pancreatic epithelial cysts derived from PPs. This system allowed to monitor establishment of pancreatic epithelial polarity and lumen formation in cellular and sub-cellular resolution in a dynamic time-resolved fashion. Furthermore, both mouse and human pancreatic cysts were able to differentiate towards the endocrine fate. This differentiation system together with scRNA-seq analysis revealed how apical-basal polarity and tight and adherens junctions change during endocrine differentiation. Conclusions: We have established a simple 3D pancreatic cyst culture system that allows to tempo-spatial resolve cellular and subcellular processes on the mechanistical level, which is otherwise not possible in vivo.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cell polarity; Cell–cell adhesion; Endocrinogenesis; Pancreatic progenitors; scRNA-seq; Three dimensional (3D)